STRENGTHENING THE CAPACITY OF PURPLE SWEET POTATO CHIPS MSMES THROUGH DIGITALIZATION OF FINANCIAL MANAGEMENT AND MARKETING IN THE TECHNOLOGY ERA - Fatimah Fatimah; Rahmawati Rahmawati; Deasy Soraya A Aminartha Putri; Arfianty Arfianty; Nasrullah A; Dwi Ananda; Alvira Alvian (MALLOMO: Journal of Community Service, 2026)
This community service activity aims to increase the business capacity of the "3 Saudara" Purple Sweet Potato Chips MSME through business legality assistance (Halal and P-IRT), the implementation of Focus Group Discussions (FGDs) with partners and the community, and assistance in financial management and digital marketing. The implementation method was carried out in stages over eight months with a participatory approach. The results of the activity showed that partners succeeded in obtaining business legality in the form of halal certification and P-IRT numbers, improving understanding of digital-based financial management, and expanding marketing reach through social media. This program has an impact on increasing consumer trust, increasing sales, and increasing product competitiveness.